Exploring the Role of MEFV Gene Mutations in Pediatric Drug-Resistant Epilepsy - Habibi, Atefeh; Raeeskarami, Seyyed Reza; Hadipour, Fatemeh; Hadipour, Zahra; Salehzadeh, Farhad; Badv, Reza Shervin; Ziaee, Vahid; sadeghi, payman (Iranian Journal of Child Neurology, 2025)
Objectives: Despite the advancements in antiepileptic drugs over the past decades, drug-resistant epilepsy (DRE) remains a significant challenge, particularly in children. Familial Mediterranean fever (FMF), attributed to mutations in the Mediterranean fever (MEFV) gene, has been linked to various neurological disorders, including seizures. This study investigates the potential association between MEFV gene mutations and DRE and evaluates their impact on the disease course. Materials & Methods: A case-control study was conducted involving 22 children under 18 years of age with DRE, referred to the Pediatric Neurology Clinic of Children’s Medical Center, Tehran, Iran, between March 2021 and March 2022. The control group comprised 30 healthy individuals randomly selected from the FMF database of Ardabil University, Iran. Relevant information, including age, demographics, disease characteristics, and treatment details, was collected using a structured form. Blood samples were analyzed for 12 common MEFV gene mutations Results: Out of 52 subjects, the case group consisted of 22 children diagnosed with DRE, compared to 30 patients without FMF in the control group. The mean age of the case group was 9.2 ± 4.5 years, with a mean age at seizure onset of 38.13 ± 32.21 months. MEFV mutations were identified in eight patients (15.4%), with seven in the control group and one (4.5%) in the case group. However, the difference in MEFV gene mutations between the case and control groups did not reach statistical significance (P=0.13). Conclusion: The prevalence of MEFV gene mutations in children with DRE was 4.5%, suggesting that these mutations may not significantly influence the occurrence of DRE in this population.